Respon Pemberian Ethyl Methane Sulfonate Terhadap Kualitas Salak Pondoh - Nandariyah Nandariyah; Sukaya Sukaya; Via Liesdiana (Universitas Sebelas Maret, 2017)
This research was conducted in Tapansari snakefruit plantation, Pakem, Sleman, Yogyakarta. This study use Completely Randomized Design with one factor. Factor used is the EMS concentration (K) difference that consists of 5 levels concentration of 0%, 0.5%, 1%, 1.5%, and 2%. The treatment is given to the female flowers from the tip to the base as much as 5 ml in each before pollination. The data were analyzed using descriptive analysis and analysis of variance by the F test level of 5% and continued by DMRT level of 5%. The result showed that application of EMS in the female flowers before pollination can reduce the size of some snakefruit sample in 1%, 1.5%, and 2% concentrations; however, it did not show significant effect on the seed size reduction. The application of EMS does not able to produce seedless snakefruits.